2016
DOI: 10.1038/srep36579
|View full text |Cite|
|
Sign up to set email alerts
|

Pathophysiological mechanisms underlying phenotypic differences in pulmonary radioresponse

Abstract: Differences in the pathogenesis of radiation-induced lung injury among murine strains offer a unique opportunity to elucidate the molecular mechanisms driving the divergence in tissue response from repair and recovery to organ failure. Here, we utilized two well-characterized murine models of radiation pneumonitis/fibrosis to compare and contrast differential gene expression in lungs 24 hours after exposure to a single dose of whole thorax lung irradiation sufficient to cause minor to major morbidity/mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Radiation doses of 8, 10, 12, and 14 Gy WTLI were assayed at 1, 3, and 6 days post-exposure. We selected the time course of the current proteomic study based upon recent publications from our team (Jackson et al 2016;. One of the recent studies in the murine WTLI model reported that ultrastructural damage and gene expression profiles suggest the response to radiation within the first 24 h post-exposure determines tissue fate .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Radiation doses of 8, 10, 12, and 14 Gy WTLI were assayed at 1, 3, and 6 days post-exposure. We selected the time course of the current proteomic study based upon recent publications from our team (Jackson et al 2016;. One of the recent studies in the murine WTLI model reported that ultrastructural damage and gene expression profiles suggest the response to radiation within the first 24 h post-exposure determines tissue fate .…”
Section: Methodsmentioning
confidence: 99%
“…One of the recent studies in the murine WTLI model reported that ultrastructural damage and gene expression profiles suggest the response to radiation within the first 24 h post-exposure determines tissue fate . The other recent study interrogated gene expression changes and interpreted them in terms of pathophysiological mechanisms (Jackson et al 2016). The study design of the proteomics study described herein was intended to assay proteomic changes on a similar timescale as these gene expression studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In WTLI studies, there was no difference in 180-day survival between males and females in C57L/J mice. In contrast, a clear sex difference was observed in the C57BL/6J mice exposed to WTLI, with females 3.54 times more likely to succumb to mortality compared to 1.62 in males (Jackson et al 2016). A marked sex-bias has also been observed when other endpoints are queried (Narendran et al 2019).…”
Section: Sexmentioning
confidence: 98%